Material Culture and Religion: Perspectives over Time - Silva, Fátima Matos; Borges, Isabel; Albuquerque, Helena (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The materialisation of religiosity has been expressed since prehistoric times through material culture. This material culture serves as a tangible embodiment of faith, communicating the diversity of human spiritual experiences. It encompasses a wide range of objects, structures, symbols, and practices that not only shape religious identities, but also reflect the evolving nature of human society. This interaction between religious beliefs and their material expressions enables an understanding of the role of religion in shaping human culture and identity. Through 13 different approaches, this reprint aims to present a cross-cultural analysis of religiosity. Its main objective is to recognise the importance of this materialisation in the knowledge of different religions, as well as to maintain, preserve, and safeguard this diverse and rich heritage for future generations.